Radio Observations Of A Nearby Type IIP SN 2012aw. Issue Volume 9:Issue S296(2013) (29th January 2014) - Yadav, Naveen; Ray, Alak; Chakraborti, Sayan; Stockdale, Christopher; Chandra, Poonam; Smith, Randall; Roy, Rupak; Dwarkadas, Vikram; Sutaria, Firoza; Pooley, Dave; Kumar, Brijesh; Bose, Subhash
Abstract: SN 2012AW is a type-IIP supernova which exploded in M95. In this paper we discuss the radio observations of this supernova and model them to determine the important parameters relevant to the explosion and the evolution of blast wave. We also determine the dominant cooling process important to this source.